Building WF16: construction of a Pre-Pottery Neolithic A (PPNA) pisé structure in Southern Jordan. (July 2015) - Flohr, Pascal; Finlayson, Bill; Najjar, Mohammad; Mithen, Steven
<x content-type="archive" xml:space="preserve">Abstract</x> The Pre-Pottery Neolithic A (PPNA) period in South-west Asia is essential for our understanding of the transition to sedentary, agricultural communities. Developments in architecture are key to understanding this transition, but many aspects of PPNA architecture remain elusive, such as construction techniques, the selection of building materials and the functional use of space. The primary aim of the research described within this contribution was to build a PPNA-like structure in order to answer questions about PPNA architecture in general, while specifically addressing issues raised by the excavation of structures at the site of WF16, southern Jordan. The second aim was to display a 'PPNA' building to visitors in Wadi Faynan to enhance their understanding of the period. The experimental construction based on one of the WF16 structures showed that (1) required materials can be acquired locally; (2) a construction technique using mud layers as described in this paper was most probably used; (3) flat, or very slightly dome-shaped, roofs are functional and can also be used as a solid working platform; (4) the WF16 small semi-subterranean buildings appear inappropriate for housing a nuclear family unit.